Optimal foraging and predator-prey dynamics III - Krivan, Vlastimil; Eisner, Jan (Theoretical population biology, 2003)
In the previous two articles (Theor. Popul. Biol. 49 (1996) 265-290; 55 (1999) 111-126), the population dynamics resulting from a two-prey-one-predator system with adaptive predators was studied. In these articles, predators followed the predictions of optimal foraging theory. Analysis of that system was hindered by the incorporation of the logistic description of prey growth. In particular, because prey self-regulation dependence is a strong stabilizing mechanism, the effects of optimal foraging could not be easily separated from the effects of bottom-up control of prey growth on species coexistence. In this article, we analyze two models. The first model assumes the exponential growth of both prey types while the second model assumes the exponential growth of the preferred prey type and the logistic growth of the alternative prey type. This permits the effect of adaptive foraging on two-prey-predator food webs to be addressed. We show that optimal foraging reduces apparent competition between the two prey types, promotes species coexistence, and leads to multiple attractors.
Keywords: populační dynamika; Animals; ekosystém; Population Dynamics; Ecosystem; lidé; predátorské chování; teoretické modely; zvířata; Predatory Behavior; Models, Theoretical; Humans